ANALISIS PERBANDINGAN KINERJA KEUANGAN PT BPR SEJAHTERA BATAM MENGGUNAKAN LABA RUGI DAN EVA - Nurul Yusyawiru; Indra Firdiyansyah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
The purpose of this research is to measure the financial performance of PT BPR SEJAHTERA BATAM using the profit and loss approach and Economic Value Added (EVA). The research method used is descriptive qualitative analysis. This study uses secondary data in the form of the financial statements of PT BPR SEJAHTERA BATAM in 2019, 2020 dan 2021 which are registered with the Financial Services Authority (OJK). The results of the study indicate that ROA and ROE tend to rise and the Economic Value Added (EVA) obtained by PT BPR SEJAHTERA BATAM for three years is positive. Positive Economic Value Added indicates that there has been a process of adding economic value to the company because the company has paid its obligations to creditors and shareholders